A comparative analysis of body composition assessment by BIA and DXA in children with type II and III spinal muscular atrophy - Wang, Wenqiao; Feng, Yijie; Long, Qi; Chen, Fei; Chen, Yuzhi; Ma, Ming; Mao, Shanshan (Frontiers in Neurology, 2022)
Background: Body composition analysis is a valuable tool for assessing and monitoring the nutritional status of children with spinal muscular atrophy (SMA). This study was designed to compare the consistency of two body composition measurements methods in children with type II and III SMA, namely, dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance analysis (BIA). Methods: From 2019 to 2021, we performed a retrospective analysis of body composition by DXA and BIA measurements methods in patients with type II and III SMA treated at a Chinese tertiary children’s hospital. Fat mass (FM), muscle mass (MM), bone mineral content (BMC), and visceral fat area (VFA) were compared using paired-sample t-tests. We calculated Lin’s concordance correlation coefficient (CCC) and spearman correlation coefficient to verify the correlation between DXA and BIA measurements. Bland–Altman analysis was used to assess the consistency of the two methods. Results: Fifty-seven children with type II and III SMA were recruited. Compared to body composition measured by DXA, the average FM measured by BIA is significantly lower (p < 0.001), whereas the average MM, BMC, and VFA measured by BIA are significantly higher (p < 0.001) in SMA children. Correlation analysis indicated strong correlation of MM (CCC = 0.96 [95% confidence interval (CI)= 0.93–0.98], r = 0.967 [p < 0.0001]) and FM (CCC = 0.95 [95% CI = 0.92–0.97], r = 0.953 [p < 0.0001]) measurements between the two methods. The Bland–Altman analysis suggests good consistency of body composition measurements between the two methods. In addition, differences in MM and VFA measurements between BIA and DAX increased according to patients’ increasing height, whereas differences in FM and BMC did not differ with height. Conclusions: The BIA measurements in SMA patients were found to be in good agreement with DXA measurements, especially for FM and MM, which are essential parameters for the nutritional evaluation of SMA children. Compared to DXA, BIA is a noninvasive, easy-to-use and repeatable measuring tool that is expected to be widely used in SMA children.